ANALISIS PENERAPAN PENDEKATAN DEEP LEARNING DIMENSI PENALARAN KRITIS DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low critical reasoning abilities of students in Pancasila Education learning in elementary schools due to the teacher-centered learning. This study aims to describe the application of the deep learning approach in developing students' critical reasoning. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation at SDN 75/I Pasar Terusan. Data analysis was carried out through data reduction, presentation, and drawing conclusions with validity testing through triangulation. The results show that the deep learning approach is able to support the development of students' critical reasoning through meaningful and reflective learning. However, its implementation is not optimal due to limitations in time, teacher understanding, and supporting facilities.